Ketogenic Diet in Neonates with Drug-Resistant Epilepsy: Efficacy and Side Effects—A Single Center's Initial Experience - Falsaperla, Raffaele; Sortino, Vincenzo; Collotta, Ausilia Desiree; Privitera, Grete Francesca; Palmeri, Antonio; Mauceri, Laura; Ruggieri, Martino (Neuropediatrics, 2023)
Background For patients with pharmacoresistant epilepsy, a therapeutic option is ketogenic diet. Currently, data on young infants are scarce, particularly during hospitalization in the neonatal intensive care unit (NICU).Objective The aim of the present study was to evaluate the short-term (3-month) efficacy and side effects of ketogenic diet in infants with “drugs-resistant” epilepsy treated during NICU stay.Methods This retrospective study included infants aged under 2 months started on ketogenic diet during NICU hospitalization to treat drug-resistant epilepsy from April 2018 to November 2022.Results Thirteen term-born infants were included, three (23.1%) of whom were excluded because they did not respond to the ketogenic diet. Finally, we included 10 infants. Six (60%) patients took three antiepileptics before starting the ketogenic diet, while four (40%) took more drugs. Diet had a good response in four (40%) patients. In four patients, the ketogenic diet was suspended because of the onset of serious side effects. The emetic levels of sodium, potassium, and chlorine, pH, and onset of diarrhea, constipation, and gastroesophageal reflux showed significant differences. Ketonuria was higher and blood pH lower in the group that took more than three drugs than in the group taking fewer than three drugs.Conclusion The ketogenic diet is efficacious and safe in infants, but the early and aggressive management of adverse reactions is important to improve the safety and effectiveness of the ketogenic treatment.
Keywords: ketogenic diet; neonates; drug-resistant epilepsy